2010
DOI: 10.1021/jp104128j
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional (2+n) REMPI of CH3Br: Photodissociation Channels via Rydberg States

Abstract: (2+n) resonance enhanced multiphoton ionization (REMPI) spectra of CH(3)Br for the masses H(+), CH(m)(+), (i)Br(+), H(i)Br(+), and CH(m)(i)Br(+) (m = 0-3; i = 79, 81) have been recorded in the 66 000-81 000 cm(-1) resonance energy range. Signals due to resonance transitions from the zero vibrational energy level of the ground state CH(3)Br to a number of Rydberg states [Ω(c)]nl;ω (Ω(c) = 3/2, 1/2; ω = 0, 2; l = 1(p), 2(d)) and various vibrational states were identified. C((3)P) and C*((1)D) atom and HBr interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Comparison of this structure with the one-photon absorption spectrum, , which has been interpreted as being due to transitions of halogen lone-pair pπ electrons to sσ Rydberg orbitals, shows no clear correspondence between the two spectra. This suggests that the Rydberg states resonantly excited by two photons do not correspond to sσ Rydberg orbitals but rather to pπ and dπ Rydberg orbitals, analogous to what is found for resonance excitation of the monohalomethanes. , …”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…Comparison of this structure with the one-photon absorption spectrum, , which has been interpreted as being due to transitions of halogen lone-pair pπ electrons to sσ Rydberg orbitals, shows no clear correspondence between the two spectra. This suggests that the Rydberg states resonantly excited by two photons do not correspond to sσ Rydberg orbitals but rather to pπ and dπ Rydberg orbitals, analogous to what is found for resonance excitation of the monohalomethanes. , …”
Section: Resultsmentioning
confidence: 52%
“…In addition to being of interest for fundamental studies of photofragmentation processes in molecules, these compounds and their photofragmentation species are of great importance in both atmospheric chemistry and astrochemistry. 10−14 Our recent REMPI studies of methyl bromide 4 and CF 3 Br 6 confirmed and added information relevant to their Rydberg state structures and dissociation dynamics. The data revealed clear photodissociation processes to form bromine atoms in both cases.…”
Section: ■ Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Thus it will resemble analogous findings for other Br-containing compounds. 32 The three strong bromine atomic lines observed in the spectral region discussed here (see above) are all observed in an excitation region corresponding to the low energy tail of the weak A-band spectrum where one-photon absorption cross section is very low, of the order 10 −21 cm 2 molecule −1 at room temperature (to be compared with the cross section of about 2.5 × 10 −18 cm 2 molecule −1 for the maximum of the A-band 33 ) (see Fig. 1).…”
Section: Bromine Atomic Linesmentioning
confidence: 99%